YouTube Da’wah Viewing and Student Religious Commitment: Menonton Dakwah YouTube dan Komitmen Beragama Mahasiswa - Nur Rahmah; Muhammad Anshar (Academia Open, 2026)
General Background: The rapid expansion of digital media has transformed religious communication, positioning YouTube as a prominent platform for Islamic da’wah among university students. Specific Background: Within Islamic higher education, students increasingly access da’wah videos that combine visual, auditory, and spiritual messages aligned with contemporary digital lifestyles. Knowledge Gap: Despite growing digital da’wah consumption, empirical studies specifically examining YouTube viewing intensity in relation to religious commitment among Islamic university students remain limited. Aims: This study aims to examine the relationship between watching Islamic da’wah videos on YouTube and religious commitment among students of UIN Alauddin Makassar. Results: Using a quantitative survey approach and simple linear regression analysis, the findings demonstrate a positive and statistically significant relationship between the intensity of watching da’wah videos and students’ religious commitment, with a moderate correlation level. Novelty: The study strengthens empirical evidence on digital da’wah by focusing on viewing intensity as a measurable variable linked to religious commitment within the context of Islamic higher education in Indonesia. Implications: These findings underline the strategic role of YouTube as a contemporary da’wah medium supporting students’ religious awareness, consistency, and practice, while also providing a reference for future digital da’wah development in Islamic universities. Highlights • Higher da’wah video viewing intensity corresponds with stronger student religious commitment• YouTube functions as an active medium for fulfilling students’ spiritual needs• Digital da’wah aligns with communication theories emphasizing active media use Keywords YouTube; Digital Da’wah; Religious Commitment; Islamic Students; Viewing Intensity